2019
DOI: 10.1002/ece3.5217
|View full text |Cite
|
Sign up to set email alerts
|

Bees and flowers: How to feed an invasive beetle species

Abstract: Invasive species may exploit a wide range of food sources, thereby fostering their success and hampering mitigation, but the actual degree of opportunism is often unknown. The small hive beetle (SHB), Aethina tumida, is a parasite of honeybee colonies endemic to sub‐Saharan Africa. SHBs have now spread on all habitable continents and can also infest colonies of other social bees. To date, the possible role of solitary bee nests as alternative hosts is unknown. Similarly, flowers as possible alternative food so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…Therefore, within the predicted current and future range expansion of SHB presented here, honey bee colonies will inevitably be present and thus potentially exposed to this pest species. Moreover, SHBs infest colonies of other social bees as well (Cervancia et al, ; Greco et al, ; Spiewok & Neumann, ) and may also use solitary bees as hosts (Gonthier et al, ). Even though the impact and its magnitude are unknown for many social bees, the predicted invasion risk could have a broad impact on this important group of pollinators and the ecosystem service they provide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, within the predicted current and future range expansion of SHB presented here, honey bee colonies will inevitably be present and thus potentially exposed to this pest species. Moreover, SHBs infest colonies of other social bees as well (Cervancia et al, ; Greco et al, ; Spiewok & Neumann, ) and may also use solitary bees as hosts (Gonthier et al, ). Even though the impact and its magnitude are unknown for many social bees, the predicted invasion risk could have a broad impact on this important group of pollinators and the ecosystem service they provide.…”
Section: Discussionmentioning
confidence: 99%
“…However, knowledge of the potential effects of climate change on such species is currently lacking (Le Conte & Navajas, 2008). The small hive beetle (SHB, Aethina tumida, Murray) is a long known parasite of social bee colonies (honey bees: A. mellifera (Lundie, 1940); Apis cerana (Cervancia, Guzman, Polintan, Dupo, & Locsin, 2016), bumblebees: Bombus impatiens (Spiewok & Neumann, 2006), stingless bees: (Greco et al, 2010) native to sub-Saharan Africa, which can also infest nests of solitary bees (Megachile rotundata, Gonthier et al, 2019). Since 1996, SHB has become an invasive species and has established local populations on every continent except Antarctica (Neumann et al, 2016;Schäfer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The geographic expansion of the invasive SHB to temperate climatic zones means that it can now also encounter various bumble bee species, whose colonies it is able to invade (Hoffmann et al, 2008). Not least, it has been recently shown that SHBs can also complete an entire life cycle in association with nests of solitary bees Megachile rotundata (Gonthier et al, 2019). Since SHB is a replicative host or biological vector for DWV (Eyer et al, 2009), such invasion may result in the transmission of viruses among bee species.…”
Section: Vector-mediated Transmissionmentioning
confidence: 99%
“…Previous studies mainly focused on survival of laboratory-reared adult SHB maintained with water as negative controls (Schmolke, 1974 (RSA); Ellis, Neumann, et al, 2002 TA B L E 1 Mortality of laboratoryreared and field-collected adult small hive beetles, Aethina tumida, under starvation from the endemic range in Africa and from the invasive range in North America up to 14 days (Ellis, Neumann, et al, 2002), 19 days (Schmolke, 1974), 19 days (Gonthier et al, 2019), and 26 days (Buchholz et al, 2008); this overall corresponds with the results reported here. However, these previous studies used varying methods and did neither compare freshly emerged laboratory-reared versus field-caught adults, males versus females nor endemic versus invasive ranges of SHB.…”
Section: Discussionmentioning
confidence: 99%
“…Small hive beetle (SHB), Aethina tumida, is an invasive species originating from sub-Saharan Africa (Lundie, 1940) that has spread almost globally (Neumann, Pettis, & Schäfer, 2016;Ouessou Idrissou, Huang, Yañez, & Neumann, 2019). The SHB lives in association with honey bee colonies, but can also infest colonies of other social bees as well as solitary bee nests (Gonthier et al, 2019;Neumann et al, 2016). Inside host nests, SHB adults can feed themselves on honey, pollen, host brood, dead or live adult bees or tricking honey bee workers into trophallactic feeding, mate and reproduce (Neumann et al, 2016).…”
Section: Introductionmentioning
confidence: 99%